Комунікативна компетенція майбутніх економістів - Шлєіна, Людмила Іванівна (Запоріжжя : 2023, 2023)
UA: У дослідженні розглянуто проблему розвитку підприємницької компетентності майбутніх економістів в аспекті навичок комунікації. Приділено увагу ролі комунікативної компетенції як необхідного елементу для професійного зростання майбутніх кваліфікованих робітників в умовах економічних викликів сьогодення. EN: The paper considered the problem of developing entrepreneurial competence of future economists in the aspect of communication skills. Attention is paid to the role of communicative competence as a necessary element for the professional growth of future skilled workers in the conditions of today's economic challenges.
Keywords: підприємницька компетентність; комунікативна компетентність; комунікація; entrepreneurial competence; communicative competence; communication